An innovative model of mentoring teachers in Jewish day schools: A pathway to professional development and teacher well-being. Issue 1 (30th September 2019) - Winter, Jeffrey S.; Bressman, Sherri; Efron, Efrat Sara
Abstract : Purpose: The purpose of this paper is to describe an innovative model of mentoring that evolved over the past ten years as a result of experience, research and self-study. This research, conducted in Orthodox Jewish day schools will raise awareness of potential benefits of mentoring as an effective means for supporting Q1 teachers' classroom effectiveness and sense of well-being. Background research is presented on mentoring as a powerful tool in supporting teachers throughout their careers. An original aspect of this paper is the analysis of exemplary cross-cultural mentoring intentional training, ongoing support and solicitation of feedback. Findings are based on samples from data collected over several years and are analyzed using qualitative tools. The authors discuss implications from two published self-studies of an exemplary mentoring model in which mentors worked with teachers and explore considerations for teacher well-being. Design/methodology/approach: A qualitative–narrative approach was chosen for these studies. The findings were drawn from three sources of data: open-ended questionnaires, end-of-year letters teachers wrote to their principals reporting on changes in their classroom practices and in-depth, semi-structured interviews conducted with teachers, mentors and administrators in each of the schools participating in the program. Findings: The two self-studies, in tandem with the teachers' surveys and reflections, illustrate how the teachers viewed the connection between the mentoring they received and their own professional growth. Overall, teachers reported a general satisfaction as a result of participating in the mentoring program. Many noted that the program provided a useful framework offering a personalized approach to their professional development. The teachers were directed to frame their own learning agendas by setting their own instructional improvement goals and asking meaningful questions relevant to their particular classroom situations. Research limitations/implications: Limited sample size and private religious school environment might put limits on implications. Practical implications: The presented model has universal implications. A personalized mentoring model, with supplementary professional development sessions geared toward topics supporting well-being, can be applied in any educational setting. Schools leaders must find ways to foster teacher satisfaction and keep teachers engaged in their own learning. Offering teachers a personalized approach that supports continued growth while encouraging them to set their own learning agendas can serve as a vital bridge to teacher satisfaction and well-being. Social implications: The findings of this paper have implications for school improvement, cross-cultural mentoring, mentor training and teacher well-being. Originality/value: Original aspects of this paper include: the self-study of exemplary mentoring program, application of mentoring in cross-cultural environments, teacher well-being in private schools and mentoring of teachers in Orthodox Jewish schools.